PERSEPSI MASYARAKAT PADA IMPLEMENTASI PERDA NOMOR 12 TAHUN 2008 BAB III PASAL 3 TENTANG KETERTIBAN SOSIAL (STUDI KASUS PEMBERIAN SUMBANGAN) - Hasanal Abdurrahman; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Less of participation and competence about awareness of law especially local regulation no. 12, 2008 chapter III paragraph 3 among society are caused by socialization process or counseling that not intensively conducted. Beside that, less of education also cause vagrants and beggars are not well aware of that local regulation. Because people give donation to the vagrants and beggars, it makes them like living in Pekanbaru, getting much money without working hard.The concept of theory used is stated by Miftah Thoha about how that perception can be seen from four sub processes, those are: 1. Stimulation/present situation, 2. Registration, 3. Interpretation, 4. Feedback. In his theory, he states several factors that affect someone perception, such as: internal factor and external factor. This research was conducted in Pekanbaru and Social and Funeral Services of Pekanbaru. This research methodology was qualitative with descriptive data analysis. In collecting the data, the researcher used interview, observation and documentation by using key informan as resources. To get that informan, the researcher used Snowball Sampling method.The result of this research can be concluded that perception of society about implementation of local regulation no. 12, 2008 chapter III paragraph 3 that discuss about social order of donation is not good enough. So, the government of Pekanbaru should socialize more about the importance of local regulation no. 12, 2008 chapter III paragraph 3 and can give strick punishment to everybody who break that regulation and controll the present of vagrants and beggars in Pekanbaru.Keywords: Perception, society, vagrants and beggars